Graffiti, Street Art and Murals Against the Neoliberal City: Wall-Written Dissensus - Abram, Sandi (Street Art & Urban Creativity, 2024)
The text explores graffiti, street art, and murals in the context of the neoliberal city, highlighting the transformation of these forms in the context of growing commodification, touristification and gentrification of urban space. Through an ethnographic research in Ljubljana (Slovenia), the study illuminates the wall-written dissensus against the current production of abstract space. Special attention is given to the visual transformation in autonomous zones, especially how squatter communities, and in particular an anarcha queer feminist group, use graffiti and street art as media for voicing radical activism, while relying on collective muralism to build a political community. The paper argues for a nuanced understanding of the role of graffiti, street art and murals in the context of the neoliberal city and within social movements, emphasizing the multi-layered nature of political graffiti and street art as a form of radical political activism.